The first close‐up images of Jupiter's polar regions: Results from the Juno mission JunoCam instrument. Issue 10 (25th May 2017) - Orton, Glenn S.; Hansen, Candice; Caplinger, Michael; Ravine, Michael; Atreya, Sushil; Ingersoll, Andrew P.; Jensen, Elsa; Momary, Thomas; Lipkaman, Leslie; Krysak, Daniel; Zimdar, Robert; Bolton, Scott
Abstract: During Juno's first perijove encounter, the JunoCam instrument acquired the first images of Jupiter's polar regions at 50–70 km spatial scale at low emission angles. Poleward of 64–68° planetocentric latitude, where Jupiter's east‐west banded structure breaks down, several types of discrete features appear on a darker background. Cyclonic oval features are clustered near both poles. Other oval‐shaped features are also present, ranging in size from 2000 km down to JunoCam's resolution limits. The largest and brightest features often have chaotic shapes. Two narrow linear features in the north, associated with an overlying haze feature, traverse tens of degrees of longitude. JunoCam also detected an optically thin cloud or haze layer past the northern nightside terminator estimated to be 58 ± 21 km (approximately three scale heights) above the main cloud deck. JunoCam will acquire polar images on every perijove, allowing us to track the state and evolution of longer‐lived features. Key Points: The JunoCam instrument obtained the first close‐up images of Jupiter's polar regions with spatial scales of 50–70 km The color and morphology of features in polar regions are very different from lower latitudes and are unlike Saturn's polar regions The altitude of a haze layer above the main cloud deck in Jupiter's atmosphere was measured using JunoCam's view of the terminator